ANALISIS PERLINDUNGAN HUKUM TERHADAP KORBAN SALAH TANGKAP DALAM TINDAK PIDANA PEMBUNUHAN DALAM PERKARA NOMOR 131PK/PID.SUS/2016 - Ardian, Mustika Saraswati; Deliana, Evi; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Protection of human rights, in essence, protection of victims, includingvictims of wrongful arrests, is a manifestation of respect for, upholding andguaranteeing human rights. Based on case No. 1131 / PID.AN / 2013 /PN.JKT.SEL, No. 360 / PID / 2013 / PT.DKI, No. 188K / PID.SUS / 2014, No. 131PK / PID.SUS / 2015 murder cases that were suspected of 4 victims, whoworked as street singers who were ultimately found not guilty, causing losses tothe victim. This type of research can be classified in normative legal research, namelylegal research conducted by researching library materials. This study examinesthe subject matter in accordance with the scope and identification of the problemthrough a statute approach carried out by examining the laws and regulationsthat relate to the legal issue under study. Data collection techniques used in theNormative Legal Research are library research methods (library research) whichuses the library as a means of collecting data, by studying books as referencematerial related to the problems to be studied. The conclusion that can be obtained from the results of the research is thatlegal protection for victims of wrongful arrest in the crime of murder in caseNumber 131PK / Pid.Sus / 2016 has not been fully implemented properly. Thiscan be seen from several provisions inside and outside which are firm and clear, however at the level of implementation it has not been fully implemented properly. Fikri, Fatahillah, Ucok and Pau who are victims of the wrongful arrests of theMurder case have so far not been able to access justice for the losses that befellhim (materially physically and psychologically). Ef orts to restore the rights of thevictim who was wrongly arrested in case Number 131PK / Pid.Sus / 2016 in amurder crime case can be made through a request for compensation andrehabilitation. However, requests for compensation and rehabilitation have notbeen implemented properly. Access to compensation and rehabilitation is still notfully implemented. This is further exacerbated regarding who has to paycompensation. Keywords: Legal Analysis, Victims, Wrong Arrests, Crime